Effectiveness of Family Planning Counseling in Improving Knowledge among Women Not Using Contraception in the Working Area of Siatas Barita Community Health Center, North Tapanuli Regency 2025 - Naomi Isabella Hutabarat; Dimpu Rismawaty Nainggolan (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Insufficient understanding and misconceptions about contraceptive techniques may impede women's capacity to make educated reproductive health choices. This study investigated short-term alterations in family planning knowledge subsequent to counseling among women not utilizing contraception in the jurisdiction of Siatas Barita Community Health Center, North Tapanuli Regency, Indonesia. A pre-experimental one-group pretest-posttest study was executed in Pancurnapitu Village from July to December 2025. A total of 53 women aged 20 to 49 years, who were not utilizing contraception, were recruited via convenience sampling. The assessment of family planning knowledge was conducted prior to counseling and 12 days post-intervention utilizing a structured 10-item true-or-false questionnaire. Total scores were categorized as good knowledge, assigned a code of 1, or poor knowledge, assigned a code of 2; hence, a lower mean coded score signified superior knowledge. Differences between pre-intervention and post-intervention scores were examined utilizing a paired-samples t-test. The average coded knowledge score diminished from 1.74 ± 0.445 prior to counseling to 1.40 ± 0.494 subsequent to therapy, resulting in a mean difference of 0.34 points. The decrease in scores, which signified enhanced knowledge, demonstrated an improvement in family planning knowledge subsequent to counseling (p < 0.001). Furthermore, 35 women (66.04%) indicated a willingness to utilize contraception but had not obtained consent or support from their husbands or family members. Family planning counseling correlated with enhanced short-term knowledge in women not utilizing contraceptives. These findings endorse the use of structured, client-centered, and rights-based counseling within basic healthcare services. The lack of a control group, the application of non-probability sampling, and the brief follow-up duration constrain causal inference and generalizability. Additional controlled trials employing validated instruments, representative populations, and extended follow-up durations are necessary to ascertain if enhanced knowledge results in informed and maintained contraceptive utilization Keywords: Contraceptive Counseling, Family Planning, Health Education, Reproductive Health, Women Of Reproductive Age.